Reference value for cardiac troponin I in a multi-ethnic group - Sthaneshwar, P.; Jamaluddin, F.A.; Fan, Y.S. (Taylor and Francis, 2010)
Aim: The aim of this study was to evaluate the distribution of cardiac troponin I (cTnI) values, measured by the ADVIA TnI-Ultra method in a multi-ethnic group and to determine the imprecision of the assay. Method: The study population comprised 234 men and 208 women and the age range was 18-73 years. Recruitment was aimed at enrolling different races and comprised 186 Malays, 136 Chinese and 120 Indians. We evaluated the analytical performance the ultra sensitive cardiac troponin I (cTnI) assay. Results: The mean values for cTnI for male and female were 0.011 mu g/L and 0.010 mu g/L respectively. No significant difference was noted between male and female populations (p>0.05). The 99th percentile for ADVIA TnI-Ultra was 0.061 mu g/L. The mean values of cTn in Malay, Chinese and Indian groups were 0.011, 0.011 and 0.011 mu g/L, respectively. There was no significant difference between the different ethnic populations (p>0.05). The assay imprecision was less than 10% at concentrations higher than 0.036 mu g/L. Conclusion: ADVIA TnI-Ultra assay showed no difference in the troponin values among different ethnic groups and between males and females. Hence a single cut-off value based on the 99th percentile can be used.